The utilisation experience of the enhanced electronic signature when managing orders - Pavel A. Muzychkin (Открытое образование (Москва))
Major universities with a number of branches, located throughout the country, have joined Plekhanov Russian University of Economics and there was a problem of operational coordination of managerial decision-making, coordination of command and control of their implementation. The problem needed to be solved very quickly as many orders have to be issued in a short period. It was necessary to develop and introduce the electronic document flow system to provide coordination of the projects’ orders on the number of students at the university branches on higher education programmes, postgraduate and vocational secondary education, and ensuring legal validity of the electronic documents.Cryptography techniques, encryption standard (National State Standard, Russian Federation legislation), university’s corporate network, electronic document flow system “DELO”, enhanced electronic signature services such as Crypto Pro CSP, CARMA and EDSIGN.Electronic approval technology between the head University and its branches with the use of the enhanced unqualified electronic signature was suggested. Two ways of exchanging documents were developed and implemented in order to make the scheme work:1) Sending documents via the corporate e-mail, using National State Standard encryption.2) Document exchange via “DELO”, electronic document flow system. The first stage has provided the document exchange, using the enciphered information with the enhanced electronic signature. At the same time, the problem of creating secure data channels between the remote university branches was solved. During the second stage, when the branches were introduced into the university’s corporate network through the secure data channels, they also gained access to the “DELO”, electronic document flow system. From the end of December 2014 up to November 2016, around 3000 orders, concerning the students were entered into the system.This method was applied not only at the branches, but also at Moscow university grounds. It is used in a slightly modified way in the vocational education department, is now being implemented in Moscow colleges.The use of the enhanced unqualified electronic signature and encryption methods has allowed to organise an efficient legal way of documents’ exchange between the head University and its numerous branches. The developed technology has solved the problem of meeting deadlines to issue the orders, concerning the students and had a certain economical effect, saving mail, transport and travel expenses.